Hospital discharge reports: content and design. Issue 5994 (22nd November 1975) - Tulloch, A J; Fowler, G H; McMullan, J J; Spence, J M
Abstract : The information required by family doctors on initial and final discharge reports from hospitals was specified and 546 such reports from hospitals in Aylesbury, Amersham, Banbury, Oxford, and High Wycombe were reviewed for the availability and accessibility of important information. Several items could have been recorded better, including the name of the hospital, the specialty (or department) concerned, and the name of the consultant in charge of the case. Drug reactions seemed to be under-reported in the initial discharge reports and information about treatment on discharge was inadequate. The recording of the prognosis and information given to the patient was deficient and communication on follow-up needs to be improved. The use of obscure abbreviations was widespread. There is room for improvement in the ease of access to important information, especially the diagnostic assessment, and the time taken for final reports to reach the general practitioner.